Halfway encounters: Meeting points of colonization routes among the southern beeches Nothofagus pumilio and N. antarctica - Soliani, Carolina; Tsuda, Yoshiaki; Bagnoli, Francesca; Gallo, Leonardo Ariel; Vendramin, Giovanni Giuseppe; Marchelli, Paula (2017)
The Patagonian region is characterized by a complex biogeographic history, with evidence of deep phylogeographic breaks shared among species. Of particular interest to conservation is the nature of colonization and settlement patterns after the last glacial period, including the detection of secondary contact between different lineages and/or hybridization among related species around phylogeographic breaks. Here we studied population demography and past hybridization of two widespread tree species endemic to South America, Nothofagus pumilio and N. antarctica.